2014
DOI: 10.1016/j.jnutbio.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The dietary ingredient, genistein, stimulates cathelicidin antimicrobial peptide expression through a novel S1P-dependent mechanism

Abstract: We recently discovered that a signaling lipid, sphingosine-1-phosphate (S1P), generated by sphingosine kinase 1, regulates a major epidermal antimicrobial peptide’s [cathelicidin antimicrobial peptide (CAMP)] expression via an NF-κB→C/EBPα-dependent pathway, independent of vitamin D receptor (VDR) in epithelial cells. Activation of estrogen receptors (ER) by either estrogens or phytoestrogens also is known to stimulate S1P production, but it is unknown whether ER activation increases CAMP production. We invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 47 publications
1
30
0
1
Order By: Relevance
“…33 It has been reported that phytoestrogens such as genistein may help to prevent photo aging in human skin and promote formation of hyaluronic acid. 34 …”
Section: Effect Of Phytoestrogens On Humansmentioning
confidence: 99%
“…33 It has been reported that phytoestrogens such as genistein may help to prevent photo aging in human skin and promote formation of hyaluronic acid. 34 …”
Section: Effect Of Phytoestrogens On Humansmentioning
confidence: 99%
“…Some TFs, however, need an endogenous or exogenous ligand to induce binding/transcription. These are called nuclear receptors and several of them seem to be essential for CAMP gene expression (paper IV) (Gombart et al, 2005;Kulkarni et al, 2016;Park et al, 2014).…”
Section: Gene Regulationmentioning
confidence: 99%
“…Accordingly, we recently demonstrated that low levels of endoplasmic reticulum (ER) stress increase cellular S1P levels, directly stimulating production of a key innate immune element, CAMP [8]. We also demonstrated that stimulation of CAMP production could also be enhanced through provision of the S1P precursor, ceramide, or suppression of S1P lyase activity, a S1P degrading enzyme, using naturally-occurring small molecules [14, 26]. For example, we recently demonstrated that the naturally-occurring stilbenoid, resveratrol, and the isoflavone genistein stimulate S1P-signaled CAMP production [14, 26].…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated that stimulation of CAMP production could also be enhanced through provision of the S1P precursor, ceramide, or suppression of S1P lyase activity, a S1P degrading enzyme, using naturally-occurring small molecules [14, 26]. For example, we recently demonstrated that the naturally-occurring stilbenoid, resveratrol, and the isoflavone genistein stimulate S1P-signaled CAMP production [14, 26]. While the former stimulates production of ceramide, the latter inhibits S1P lyase activity, as well as also increasing acidic- and neutral ceramidase activity production, resulting in elevated cellular S1P levels.…”
Section: Discussionmentioning
confidence: 99%